Role of Sphingosine-1-Phosphate Phosphohydrolase 1 in the Regulation of Resistance Artery Tone - Peter, Bernhard Friedrich (2008)
Sphingosine-1-phosphate (S1P), which mediates pleiotropic actions within the vascular system, is a prominent regulator of microvascular tone. By virtue of its S1P-degrading function, we hypothesized that S1P-phosphohydrolase 1 (SPP1) is an important regulator of tone in resistance arteries. Hamster gracilis muscle resistance arteries express mRNA encoding SPP1. Overexpression of SPP1 (via transfection of a SPP1(wt)) reduced resting tone, Ca(2+) sensitivity, and myogenic vasoconstriction, whereas reduced SPP1 expression (antisense oligonucleotides) yielded the opposite effects. Expression of a phosphatase-dead mutant of SPP1 (SPP1(H208A)) had no effect on any parameter tested, suggesting that catalytic activity of SPP1 is critical. The enhanced myogenic tone that follows overexpression of S1P-generating enzyme sphingosine kinase 1 (Sk1(wt)) was functionally antagonized by coexpression with SPP1(wt) but not SPP1(H208A). SPP1 modulated vasoconstriction in response to 1 to 100 nmol/L exogenous S1P, a concentration range that was characterized as S1P(2)-dependent, based on the effect of S1P(2) inhibition by antisense oligonucleotides and 1 μmol/L JTE013. Inhibition of the cystic fibrosis transmembrane regulator (CFTR) (1) restored S1P responses that were attenuated by SPP1(wt) overexpression; (2) enhanced myogenic vasoconstriction; but (3) had no effect on noradrenaline responses. We conclude that SPP1 is an endogenous regulator of resistance artery tone that functionally antagonizes the vascular effects of both Sk1(wt) and S1P(2) receptor activation. SPP1 accesses extracellular S1P pools in a manner dependent on a functional CFTR transport protein. Our study assigns important roles to both SPP1 and CFTR in the physiological regulation of vascular tone, which influences both tissue perfusion and systemic blood pressure.